2014
DOI: 10.1093/bioinformatics/btu389
|View full text |Cite
|
Sign up to set email alerts
|

Cloud4Psi: cloud computing for 3D protein structure similarity searching

Abstract: Summary: Popular methods for 3D protein structure similarity searching, especially those that generate high-quality alignments such as Combinatorial Extension (CE) and Flexible structure Alignment by Chaining Aligned fragment pairs allowing Twists (FATCAT) are still time consuming. As a consequence, performing similarity searching against large repositories of structural data requires increased computational resources that are not always available. Cloud computing provides huge amounts of computational power t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 11 publications
2
20
0
Order By: Relevance
“…In structural alignment, [39] observed that performance degraded slightly after 8 mappers was increased to 30. Furthermore, this trend has also been observed on the MS Azure platform we have discussed for comparison -in scaling Cloud4Psi, also a structural alignment application [51], observed that horizontal scaling resulted in performance degradation as a result of an increase in nodes sharing a virtual disk, and that vertical scaling resulted in performance degradation as a result of increased CPU utilisation (due to more processes running per node).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In structural alignment, [39] observed that performance degraded slightly after 8 mappers was increased to 30. Furthermore, this trend has also been observed on the MS Azure platform we have discussed for comparison -in scaling Cloud4Psi, also a structural alignment application [51], observed that horizontal scaling resulted in performance degradation as a result of an increase in nodes sharing a virtual disk, and that vertical scaling resulted in performance degradation as a result of increased CPU utilisation (due to more processes running per node).…”
Section: Discussionsupporting
confidence: 65%
“…A similar bioinformatics SaaS (Software-as-a-Service) for structural alignment of proteins, has been developed for the Microsoft Azure platform -Cloud4Psi developed by [51]. Their service utilises three newer algorithms that are implemented in the BioJava project, and which are derived from CE (jCE), and FATCAT (jFATCAT-rigid and jFATCAT-flexible) [60].…”
Section: Structural Alignmentmentioning
confidence: 99%
“…Many hot issues in various sub-fields of bioinformatics were also solved with the use of Big Data ecosystems and Cloud computing, e.g., mapping nextgeneration sequence data to the human genome and other reference genomes, for use in a variety of biological analyzes including SNP discovery, genotyping and personal genomics [65], sequence analysis and assembly [17,30,34,35,47,62], multiple alignments of DNA and RNA sequences [86,91], codon analysis with local MapReduce aggregations [63], NGS data analysis [8], phylogeny [24,48], proteomics [37], analysis of proteinligand binding sites [23], and others. Regarding the analysis of 3D protein structures, it is worth mentioning several works, including Hazelhurst et al [20] and Małysiak-Mrozek et al [46] devoted to exploration of various atomic interactions within protein structures, works of Che-Lun Hung and Yaw-Ling Lin [25], and Mrozek et al [51,53,[55][56][57], devoted to comparison and alignment of 3D protein structures, and cloud-based system for 3D protein structure modeling presented in [54]. However, none of the mentioned works was focused on prediction of disordered regions.…”
Section: Related Workmentioning
confidence: 99%
“…The second group of approaches consists of solutions that utilize farms of computers or virtual machines to perform protein structure comparison. Examples of such solutions are MAS4PSi [27], Cloud4Psi [28,34], and CloudPSR [32]. All of them rely on fold-based methods for 3D protein structure comparison.…”
Section: Scalable Solutions For 3d Protein Structure Similarity Searcmentioning
confidence: 99%